A Case of the Endocrine Carcinoma of the Stomach Occurring Concurrently with Adenocarcinoma - Hirose, Nobuaki; Yamamoto, Hirofumi; Nishihara, Kazuyoshi; Miki, Takashi; Nagafuchi, Kazumitsu; Watanabe, Masato; Kawakami, Katsuhiko; Sanefuji, Hayato (Nippon Shokaki Geka Gakkai zasshi, 1994)
Endocrine carcinoma of the stomach is a rare disease. A 57-year-old man was admitted to our hospital complaining of an epigastric discomfort. The upper gastrointestinal series and endoscopic examinations revealed a well-demarcated tumor with an undermining ulcer in the greater curvature of the gastric antrum (a Borrmann type 2 tumor). Subtotal gastrectomy was performed with the finidngs of 2T3N1 (+) P0H0M0 in Stage IIIa. The tumor was diagnosed as an endocrine carcinoma and tumor cells were shown to have argyrophilic granules by the Grimelius stain. Furthermore, the tumor was immunohistochemically positive for chromogranin A. Postoperatively, chemotherapy using etoposide and cis-platinum was given. Endocrine carcinoma of the stomach belongs to a category different from so-called classical carcinoid, and shows a very aggressive clinical course. We suggest that patients with endocrine carcinoma of the stomach may benefit from anticancer chemotherapeutic regimens similar to those for patients with pulmonary small cell carcinoma.